The Design and Development Of Pond Water Quality Control Using pH Booster In Domestication Of Nomei Fish (Harpodon nehereus) - Rasmin, Rasmin; Prasetia, Abdul Muis; Sartika, Linda (Jurnal Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2024)
Nomei (Harpodon nehereus) is a special fish and one of the characteristic of the city of Tarakan, because it belongs to an endemic animal which is only found in coastal areas which is precisely in Juata laut water. The nutritional and protein content found in nomei fish is fery high so it is much favored by the people of Tarakan. Preventing the decline in the population level of nomei fish due to continuous fishing by fisherman so that sustainable and synergistic cultivation is needed by means of domestication. To support nomei fish domestication activities, it is carried out by implementing pond water quality control by considering two measurable parameters, namely water salinity and pH using a microcontroller as a pond water quality controller. The results of controlling the up to dwon pond water salinity decreased by 3.0316% and the down to up pond water salinity increased in salinity value by 8.18382%. for controlling the pH of pond water, the system worked very well and was able to maintain the pH value at a predetermined set point at 1:08:00 AM, 2:08:00 AM, 3:06:00 AM, 4:33:00 AM, 6:37:00 AM, 7:13:00 AM, and 3:01:00 PM with pH value between 7.5 – 8.5. The recommendation from this study indicated that the water quality control system that had been created was able to maintain and control salinity nomei fish pond according to the given set point value.  Keywords: Nomei fish (Harpodon nehereus); Domestification; Control; Salinity; pH; Microcontroller.